Electrochemical Studies of Three Dimensional Graphene Foam as an Electrode Material. Issue 6 (14th March 2017) - Zhao, Daoli; Zhang, Lu; Siebold, David; DeArmond, Derek; Alvarez, Noe T.; Shanov, Vesselin N.; Heineman, William R.
Abstract: Graphene foam is one kind of network of three dimensional (3D) graphene, which inherits the properties of two dimensional graphene and overcomes the aggregation/stacking of graphene sheets. In this work, graphene foam has been characterized by scanning electron microscopy and Raman spectroscopy. A graphene foam electrode was evaluated as a new electrode material by cyclic voltammetry (CV) and used for the detection of trace level of Pb 2+ by anodic stripping voltammetry (ASV). Under the optimized condition of deposition potential (‐1.2 V) and deposition time (2 min), the detection limit is estimated to be 40 nM for Pb 2+ based on the 3σ method. Abstract :